2023
DOI: 10.1007/s00417-023-06159-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of autologous platelet treatment for optic disc pit maculopathy

Abstract: Purpose Optic disc pits (ODPs) are rare congenital cavitary abnormalities of the optic nerve head, which can lead to serous macular detachments. The aim of this study was to evaluate the long-term efficacy of pars plana vitrectomy (PPV) combined with autologous platelet concentrate (APC) for the treatment of optic disc pit maculopathy (ODP-M). Methods A retrospective analysis was performed on eleven eyes of ten patients with ODP-M, who received PPV combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Two Italian study groups reported results on the use of human amniotic membrane to plug the disc pit during PPV, with improved visual acuity at 12 months and no fluid recurrence [ 30 , 31 ]. Gklava reported the possible use of autologous platelets, both as primary and rescue therapy, with improved functional and morphologic outcomes without relapse over a long follow-up period [ 32 ].…”
Section: Optic Disc Pitmentioning
confidence: 99%
“…Two Italian study groups reported results on the use of human amniotic membrane to plug the disc pit during PPV, with improved visual acuity at 12 months and no fluid recurrence [ 30 , 31 ]. Gklava reported the possible use of autologous platelets, both as primary and rescue therapy, with improved functional and morphologic outcomes without relapse over a long follow-up period [ 32 ].…”
Section: Optic Disc Pitmentioning
confidence: 99%